Durvalumab plus gemcitabine and cisplatin in patients with advanced biliary tract cancer: an exploratory analysis of real-world data - Olkus, Alexander; Tomczak, Aurelie; Berger, Anne Katrin; Rauber, Conrad; Puchas, Philip; Wehling, Cyrill; Longerich, Thomas; Mehrabi, Arianeb; Chang, De-Hua; Liermann, Jakob; Schäfer, Sophia; Pfeiffenberger, Jan; et al. (Targeted oncology, 2024)
The combination of gemcitabine and cisplatin (gem/cis) with the anti-PD-L1-antibody durvalumab was recently approved as first line therapy for biliary tract cancer (BTC) based on the results of the TOPAZ-1 trial.
Online veröffentlicht: 28. Februar 2024
Gesehen am 09.10.2024